View Islamic Law against Mothers Who Interfere with Children's Households in Sena Village, Batangkuis - Maswandi Maswandi; Jamillah Jamillah (Budapest International Research and Critics University, 2021)
The aims of this study is to find out the view islamic law against mothers who interfere with children's households in sena village, batangkuis. This study use qualitative research. The result shows that In Sena Village, Batangkuis, marriage is a sign of the formation of a new house which will soon separate itself, both economically and in terms of housing, separated from the parent group and forming the basis for a new household. However, in reality, as happened in the surrounding community, the role of a mother towards her child who has a family still exists. This is evidenced by the existence of several interventions by a mother in a child's household which include material problems formed from the determination of housing and additional income. Likewise, problems in immaterial which include advice on children's family problems that have not been resolved and asking a mother to help solve them.